Tiếng Hà Nội và người Hà Nội - một cách nhìn. /Trịnh Cẩm Lan,. - Trịnh, Cẩm Lan.
Locate an area of Hanoi dialect and Hanoi people, the paper deals with o point of view about two concepts of Hanoi dialect and Hanoi people by a discussion of another point of view about these concept, and bring out simultaaaaaaaaaneously an opinion terms of two variant of Hanoi dialect, those are urban Hanoi dialect and rural Hanoi dialect with their typical features.